Construction of constrained experimental designs on finite spaces for a modified Ek-optimality criterion - Uciński, Dariusz (Zielona Góra: Uniwersytet Zielonogórski)
A simple computational algorithm is proposed for minimizing sums of largest eigenvalues of the matrix inverse over the set of all convex combinations of a finite number of nonnegative definite matrices subject to additional box constraints on the weights of those combinations. Such problems arise when experimental designs aiming at minimizing sums of largest asymptotic variances of the least-squares estimators are sought and the design region consists of finitely many support points, subject to the additional constraints that the corresponding design weights are to remain within certain limits.
Keywords: constrained optimum experimental design; minimal sum of largest eigenvalues; generalized simplicial decomposition; optimal measurement selection